2010
DOI: 10.1007/s00421-010-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation does not impair kidney function in type 2 diabetic patients: a randomized, double-blind, placebo-controlled, clinical trial

Abstract: Creatine supplementation may have a therapeutic role in diabetes, but it is uncertain whether this supplement is safe for kidney function. The aim of this study was to investigate the effects of creatine supplementation on kidney function in type 2 diabetic patients. A randomized, double-blind, placebo-controlled trial was performed. The patients were randomly allocated to receive either creatine or placebo for 12 weeks. All the patients underwent exercise training throughout the trial. Subjects were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 29 publications
3
52
0
12
Order By: Relevance
“…Additionally, creatine has antioxidant properties. Preliminary studies have demonstrated it to be neuroprotective for PD patients [5254], but a different placebo-controlled study showed creatine had no effect on PD scores, dopamine transporter imaging, or non-motor symptoms of PD [55]. While the exact mechanism of creatine neuroprotection remains unclear, the ATP energy pool is tightly coupled to the creatine kinase system suggesting creatine supplementation may alter mitochondrial properties [56].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, creatine has antioxidant properties. Preliminary studies have demonstrated it to be neuroprotective for PD patients [5254], but a different placebo-controlled study showed creatine had no effect on PD scores, dopamine transporter imaging, or non-motor symptoms of PD [55]. While the exact mechanism of creatine neuroprotection remains unclear, the ATP energy pool is tightly coupled to the creatine kinase system suggesting creatine supplementation may alter mitochondrial properties [56].…”
Section: Discussionmentioning
confidence: 99%
“…Kreider et al [22] reported that creatine supplementation (5–10 g/day for 21 months) had no significant effects on creatinine or creatinine clearance in American football players. Gualono and associates [262] reported that 12 weeks of creatine supplementation had no effects on kidney function in type 2 diabetic patients. Finally, creatine supplement has been used as a means of reducing homocysteine levels and/or improving patient outcomes in patients with renal disease [263–265] as well as ameliorating birth asphyxia related renal dysfunction in mice [228].…”
Section: Safetymentioning
confidence: 99%
“…Creatine also possesses antioxidant properties and can be an effective inhibitor of mitochondrial permeability transition pore opening and mitochondrial iron accumulation. Preclinical studies in various models have demonstrated its potential role as a neuroprotective agent [104]. Recently, a neuroprotective effect of creatine was demonstrated in MPP + and 6-OHDA-treated dopaminergic neuronal cell cultures, where it protected tyrosine hydroxylase immunoreactive dopaminergic neurons and their fibers [105].…”
Section: Antioxidant Therapymentioning
confidence: 99%